A Clinical Review on Extreme Hypofractionated Stereotactic Body Radiation Therapy for Localized Prostate Cancer Using Nonrobotic Linear Accelerators. (28th May 2014) - Macias, Victor A.; Perez-Romasanta, Luis A.
<x xml:space="preserve">Abstract</x> Seven phase I–II studies fell within the inclusion criteria. Details on the radiotherapy technique, patient selection, fractionation scheme, exclusion criteria, treatment toxicity, quality-of-life, and tumor control were collected. The studies provide encouraging results of acute and late toxicity, with rare grade 3 events, that seem comparable to robotic SBRT. The biochemical disease-free survival rates look promising, but most patients belong to the low-risk group. The trials are limited by a short follow-up, small number of patients, and different approaches in prescribing dose and defining the acceptable dose heterogeneities. Currently, nonrobotic SBRT regimens should be used in the context of clinical trials.